Total Electron Content Fluctuations and Their Implications for GPS Signal Delay over Thailand: Insights from Low Latitudes during the Ascending Phase of Solar Cycle 25 - Thanapon Keokhumcheng; Prarinya Phothila; Samatchaya Maichuen; Nitipat Buakao; Jianfeng Zhang; Prasert Kenpankho (Annals of Geophysics, 2026)
This research investigates how fluctuations in Total Electron Content (TEC) on the global positioning system (GPS) affect GPS performance in Thailand’s low latitude region during the ascending phase of solar activity 25th, utilizing data from 2023 to 2025. To capture TEC variations, five GPS monitoring stations were strategically deployed along a north‑south transect across Thailand including Bangkok station, Chiang Mai station, KMITL Chumphon station, Nongbualumphu station, and Phuket station. TEC data collected from these stations were analyzed using statistical techniques with comparisons to IGS and IRI models to explore ionospheric dynamics and solar activity throughout the ascending phase of the cycle years, influencing TEC values and the time delay in the navigation system. The research reveals how solar‑induced ionospheric changes influence TEC levels and cause time delays in GPS signals, which are critical factors for satellite navigation accuracy. These insights pave the way for enhancing GPS reliability and efficiency in low latitude regions, contributing to the development of more robust global navigation systems.
Keywords: Ionosphere and magnetosphere dynamics; GNSS positioning and interference; Earthquake Detection and Analysis